Manajemen Pengembangan Kompetensi Siswa Sekolah Menengah Kejuruan Berbasis Kemitraan - Rega Eko Nur Yulian; Fery Diantoro (Edumanagerial, 2023)
Vocational High Schools are educational institutions that produce graduates who are ready to work. But in reality, many Vocational High School graduates are not ready to work because they do not have the competencies needed by the market. This study aims to examine and analyze the management of partnership-based student competency development in the software engineering department of Vocational High School through program planning, program implementation and program evaluation. This research was conducted through a descriptive qualitative approach with a case study research type. Data collection used interviews, observation, and documentation with data analysis techniques using data condensation, data presentation and conclusion drawing. Checking the validity of the data using triangulation (source, technique, time). The results of the study stated that 1) Planning carried out by the Vocational High School Software Engineering department in improving student competencies begins with competency meetings, MoUs, Curriculum Synchronization, and class learning. Student competency development activities in the form of field work practices, industry visits, and guest teachers 2) implementation of student competency development activities in field work practice activities students carry out internships for 6 months with direction, monitoring, socialization, and project creation. The implementation of guest teachers is class learning with teachers from the industry. The implementation of industrial visits has three activities, namely, industrial exploration, workshops, and study tours. 3) evaluation of field work practice activities with monitoring, project demonstrations, activity report books, student report books, and student assessments. Evaluation of guest teacher activities and industrial visits with activity report books and meetings.